Scabies Affects Quality of Life in Correlation with Depression and Anxiety - Koç Yıldırım, Sema; Demirel Öğüt, Neslihan; Erbağcı, Ece; Öğüt, Çağrı (Dermatology Practical & Conceptual, 2023)
Introduction: Scabies is a highly contagious disease affects many people worldwide each year and a major public health problem. A small number of studies have shown that scabies causes impairment in the quality of life in adult patients. Objectives: The aims of this study are to assess the impact of scabies on adult patients quality of life (QoL) and evaluate the relationship between depression and anxiety levels and impairment in life quality. Methods: This cross-sectional study included adult patients diagnosed with scabies in our dermatology outpatient clinic. The effect of scabies on QoL was evaluated by Dermatology Life Quality Index (DLQI), and the levels of depression and anxiety were evaluated by Beck Depression Scale (BDS) and Beck Anxiety Scale (BAS). Results: Totally, 85 patients included to the study. QoL of 72.2% of the patients was moderate to extremely large affected. There was a positive correlation between the duration of the disease, the total DLQI score and the severity of the disease impact on QoL (rs= 0.287, P = 0.01 and rs=0.280, P = 0.008, respectively). A positive correlation was found between the number of treatments received and the total DLQI (rs= 0.223, P = 0.042). There was a positive correlation between BDS and BAS, and total DLQI score (rs=0.448 and P = 0.000; rs=0.456 and P = 0.000, respectively). Conclusions: Scabies has a moderate to severe effect on QoL. There was a positive correlation between impairment QoL and anxiety and depression scores.